Depth of Field: Using photographs and narratives to explore and reflect on ageing. Issue 6 (1st November 2016) - Brand, Gabrielle; Miller, Karen; Wise, Steve; Saunders, Rosemary; Dugmore, Helen; Etherton-Beer, Christopher
Abstract: The learning landscape of the higher education environment is changing, with an increased focus over the past decade on how educators might begin to cultivate reflective skills in health professions students. In addition, changing professional requirements demand that health professionals are adequately prepared to practise in today's complex healthcare systems, including responding to changing demographics of population ageing. In this educational case study, we will share how we (a group of education, medical and nursing academics) developed 'Depth of Field: Exploring Ageing' a digital, consumer-driven, interprofessional reflective learning resource that uses photographs, narrative and small-group work to strengthen reflective capacity in current and/or future health professionals.